Electric buses in malaysia: Policies, innovations, technologies and life cycle evaluations - Al-Ogaili A.S.; Al-Shetwi A.Q.; Babu T.S.; Hoon Y.; Abdullah M.A.; Alhasan A.; Al-Sharaa A. (MDPI, 2023)
bus transport; electrical power; innovation; life cycle analysis; transportation policy; East Malaysia; Malaysia; Melaka; Putrajaya; Sarawak; West Malaysia